The Crude Oil “Crude Oil Treasure” Massive Loss Incident of Bank of China - Wang, Minjie (Journal of Global Economy, Business and Finance, 2025)
In April 2020, an investor who invested 10,000 RMB in crude oil when U.S. oil prices dropped to just one cent ended up owing the bank 40 million RMB. This shocking outcome was the result of a “position overrun” incident involving Bank of China’s “Crude Oil Treasure” (Crude Oil Treasure) product, which occurred against the backdrop of an unprecedented plunge in international crude oil prices into negative territory. As a consequence, a large number of long-position investors found their account balances turned negative and even faced additional compensation liabilities. The incident drew widespread attention from the public and media, revealing significant shortcomings in investor financial literacy and regulatory oversight, while also exposing critical flaws in the design and risk management of complex financial products by financial institutions. This paper employs the GARCH model to examine the volatility of crude oil futures prices, aiming to characterize the fluctuation patterns of the crude oil market and provide empirical insight into the market conditions that contributed to the event. As the first major financial product risk event in China triggered by negative international futures prices, the Crude Oil Treasure incident is both representative and serves as a stark warning.